The Double-Edge of Organizational Legitimation - Ashforth, Blake E.; Gibbs, Barrie W. (Organization Science, 1990)
Organizations require legitimacy to attract constituents' support Legitimacy, however, is always problematic. Thus, organizations frequently pursue legitimacy through a variety of substantive and symbolic practices. But legitimacy is a social judgment that is ultimately accorded the organization by its constituents. Organizations that pursue this judgement run the risk of “protesting too much”–of being perceived as precisely the opposite, manipulative and illegitimate. Such organizations include (1) the clumsy actor, perceived as unethical, heavy-handed, or insensitive, (2) the nervous actor, perceived as dogmatic, intolerant, or evasive, and (3) the overacting actor, perceived to overstate claims to legitimacy or overreact to faults. The analysis suggests that attempts to increase legitimacy may trigger a series of vicious circles which ultimately decrease legitimacy.